Pengaruh Model Advance Organizer Terhadap Pemahaman Siswa Pada Mata Pelajaran Pendidikan Pancasila Materi Norma Dalam Kehidupanku Kelas V Sekolah Dasar - Sulis Margareza; Diana Pramesti; Eka Wahyuningsih (STKIP Subang, 2025)
ABSTRACT This study was motivated by the low level of student understanding of the subject of Pancasila Education, specifically the material on norms in my life, as seen from the Learning Objective Completion Criteria, which was still below average, with only 9 out of 26 students achieving the KKTP. This study aims to determine the effect of the Advance Organizer Model on students' understanding of Pancasila Education in the subject of Norms in My Life in Grade V at SDN 8 Jebus. The approach used is quantitative with a Pre-Experimental Design and One-Group Pretest-Posttest Design. The test used is a written test consisting of 10 essay questions. The analysis used normality testing using the Shapiro Wilk test and hypothesis testing using the Paired Sample T-Test. This study proved that the pretest average score was 50.19 with a minimum score of 27.5 and a maximum score of 90, while the posttest average score was 75.09 with a minimum score of 42.5 and a maximum score of 95. The results of the data analysis prove that there is an effect of the Advance Organizer model on students' understanding of Pancasila education material on norms in my life in Grade V at SDN 8 Jebus.